2007
DOI: 10.1002/cncr.22376
|View full text |Cite
|
Sign up to set email alerts
|

Update of the decitabine experience in higher risk myelodysplastic syndrome and analysis of prognostic factors associated with outcome

Abstract: TGFβ signalling is required for normal cardiac development. To investigate which cell types are involved, we used mice carrying a floxed Type II TGFβ receptor (Tgfbr2fl) allele and Cre‐lox genetics to deplete this receptor in different regions of the heart. The three target tissues and corresponding Cre transgenic lines were atrioventricular myocardium (using cGata6‐Cre), ventricular myocardium (using Mlc2v‐Cre), and vascular endothelium (using tamoxifen‐activated Cdh5(PAC)‐CreERT2). Spatio‐temporal Cre activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 63 publications
5
59
1
1
Order By: Relevance
“…2 Overall survival of responders and non-responders survival, respectively; P=.047) as well as a favorable response duration of 64 weeks. The observed median overall survival of 74 weeks in the group of responding patients corresponds well with the survival rates from the randomized phase II/III trials published for 5-AZA as well as decitabine [8,10,13,14,19], most of which had a higher number of treatment cycles. Therefore, our results suggest that even a limited number of treatment cycles may be beneficial for patients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…2 Overall survival of responders and non-responders survival, respectively; P=.047) as well as a favorable response duration of 64 weeks. The observed median overall survival of 74 weeks in the group of responding patients corresponds well with the survival rates from the randomized phase II/III trials published for 5-AZA as well as decitabine [8,10,13,14,19], most of which had a higher number of treatment cycles. Therefore, our results suggest that even a limited number of treatment cycles may be beneficial for patients.…”
Section: Discussionsupporting
confidence: 82%
“…For responding patients, the median time to AML progression was 45 weeks (95% CI 22-68), while the median time to AML in non-responders was 14 weeks (95% CI [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. This difference was significant (P=0.038).…”
Section: Time To Aml and Overall Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…The multivariate analysis predicted shorter response duration and OS in the presence of a complex karyotype at baseline [4]. Our results are indeed similar to previous data by the MDACC (MD Anderson Cancer Center), who reported that chromosome 5 and 7 abnormalities were associated to shorter survival but not to the achievement of best response [5]. This patient group was similar, in terms of frequency of high-risk cytogenetic abnormalities (26%) and OS (median 20 months) to the series of patients enrolled in the AZA001 trial (high-risk cytogenetic abnormalities: 28% and median OS 24.4 months) [2].…”
supporting
confidence: 90%
“…Using a modification of an initial decitabine dosing regimen, two non-randomized studies in lower and higher and lower risk patients have demonstrated similar responses and survival duration to those with azaC (Kantarjian et al, 2007b;Steensma et al, 2009). The former single centre trial with 85% either higher risk or secondary MDS patients had an overall survival of 20 months, with a 2-year survival of 41%.…”
Section: Management Of Higher Risk Diseasementioning
confidence: 99%